Are patients with non-ST elevation myocardial infarction undertreated? - Gosselink AT Marcel; Hoorntje Jan CA; de Boer Menko-Jan; Dambrink Jan-Henk E; Ottervanger Jan; Rasoul Saman; Zijlstra Felix; Suryapranata Harry; van't Hof Arnoud WJ (BMC Cardiovascular Disorders, 2007)
Abstract Background The worse prognosis in patients without ST-elevation (non-STEMI) as compared to ST-elevation myocardial infarction (STEMI), may be due to treatment differences. We aimed to evaluate the differences in characteristics, treatment and outcome in patients with non-STEMI versus STEMI in an unselected patient population. Methods Individual patient data from all patients in our hospital with a discharge diagnosis of MI between Jan 2001 and Jan 2002 were evaluated. Follow-up data were obtained until December 2004. Patients were categorized according to the presenting electrocardiogram into non-STEMI or STEMI. Results A total of 824 patients were discharged with a diagnosis of MI, 29% with non-STEMI and 71% with STEMI. Patients with non-STEMI were significantly older and had a higher cardiovascular risk profile. They underwent less frequently coronary angiography and revascularization and received less often clopidogrel and ACE-inhibitor on discharge. Long-term mortality was significantly higher in the non-STEMI patients as compared to STEMI patients, 20% vs. 12%, p = 0.006, respectively. However, multivariate analysis showed that age, diabetes, hypertension and no reperfusion therapy (but not non-STEMI presentation) were independent and significant predictors of long-term mortality. Conclusion In an unselected cohort of patients discharged with MI, there were significant differences in baseline characteristics, and (invasive) treatment between STEMI and non-STEMI. Long-term mortality was also different, but this was due to differences in baseline characteristics and treatment. More aggressive treatment may improve outcome in non-STEMI patients.